(3HMQ GdahGFO aj GdefWbs
(3ChdgG (B:s
(3CeG HYO MeOkG ddg hGdKfGA Ydjg HeG gh Cgdg aEf LeGYI ef GdYdeGA GdcHGQ GdPjf GdJeShG efi GedC cJGH ai GdefWb Ydi hLg GdEjVGM hGdHjGf s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg dh cGf cPdc dUOb JHjVg hgh bhdfG HYV CaQGO cdGeg di gPg GdSGYI UGQg ChSJdRe dUObgG Ch cPHgG s
(3Hg BKGQ WeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs